Development of serological assay for detection of antibodies in the N protein of SARS-CoV-2 in human sera in Mongolia - Davaakhuu, Gantulga; Sandag, Zolzaya; Myagmar, Nomin; Oyunbat, Nomuun; Enkhtuya, Ariya; Buyanbat, Khurelsukh; Davaanyam, Maral; Boldbaatar, Tuul; Badarch, Darmaa; Tsedenbal, Naranzul; Damdindorj, Lkhagvasuren; Tsendsuren, Oyunsuren (Proceedings of the Mongolian Academy of Sciences, 2021)
The capability to detect Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection and identify immune responses among the population is crucial for managing the outbreak of the COVID-19 pandemic. Although PCR-based nucleic acid detection techniques are utilized to detect viral infection in people, alternative tests capable of distinguishing between exposure and infection are urgently needed beyond this restricted window of detectable viral replication. Antibodies are produced in human sera within a few days after viral infection, providing longer period for performing tests to acquire reliable database. Herewith, we provide the results of our in-house developed ELISA (Enzyme-Linked Immunosorbent Assay) that displays all of the properties necessary for high-throughput of human sera sample analysis. This test does not involve the handling of live viruses, although it detects a variety of antibody types in serum and plasma of human after exposure to the virus. For in-house development of the kit, the nucleocapsid (N) gene of SARS-CoV-2 virus was cloned in the prokaryotic expression vector pGEX-6P-1, and purified N protein was used to detect IgG antibodies in human sera samples. In total 76 human serum samples that were collected before novel coronavirus registry in Mongolia in March 2020, as well as 200 serum samples from patients who had been infected by SARS-CoV-2 virus, were used. Among 200 serum samples, 188 were positive and 12 were false negative, while in non-infected cases 69 were negative and 7 were false positive, suggesting 94 per cent sensitivity and 90.7 per cent specificity of the kit, with p-values of 0.02.